POLA PENGELOLAAN SEKOLAH BARU; STUDI KASUS DI KB (KELOMPOK BERMAIN) SYIFA AZZAHRA - Utama, Yudi Nanda (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
Equity in education must be realized in its implementation. In Sirambas Village, the distribution of Early Childhood Education (KB) programs remains uneven, and many community members are reluctant to enroll their children in KB, considering it unimportant and costly. This study employs a qualitative approach with a case study method. Data were collected through interviews, observations, and document analysis, then analyzed using data reduction, data presentation, and conclusion drawing. The findings at KB Syifa Azzahra in Sirambas Village reveal: (1) school management is based on the philosophy "by the people, for the people," ensuring free education; (2) management encompasses planning, organizing, leadership, and supervision; (3) funding is conducted independently; (4) teacher optimization is achieved through a guest teacher program; (5) learning emphasizes a holistic approach covering cognitive, affective, and psychomotor aspects; and (6) school promotion strategies leverage socio-cultural approaches. The success of this program is supported by active community participation, which has increased awareness of the importance of early childhood education. These findings underscore the significance of community-based approaches in expanding access, fostering equity, and creating sustainable education models.